Wholeness in Time: Vulnerability, Disability, and Sabbath Temporality - Bialek, Fannie (Journal of disability & religion, 2024)
This paper argues for the significance of time to Julia Watts Belser’s disability theology in Loving Our Own Bones. Belser’s focus on the wholeness of the present responds to significant problems in ableist conceptions of healing, which imply the insufficiency of the present self. This paper suggests how these ideas should lead to new thinking about time more broadly, encouraging a different kind of future-thinking instead of resisting it.